Pressure overload selectively increases n-3 PUFA in myocardial phospholipids during early postnatal period - Novák, František; Kolář, František; Voců, Šárka; Vecka, Marek; Nováková, Olga (Physiological research, 2012)
Increasing hemodynamic load during early postnatal development leads to rapid growth of the left ventricular (LV) myocardium, which is associated with membrane phospholipid (PL) remodeling characterized by n-3 polyunsaturated fatty acids (PUFA) accumulation. The aim of this study was to examine the influence of additional workload imposed early after birth when ventricular myocytes are still able to proliferate. Male Wistar rats were subjected to abdominal aortic constriction (AC) at postnatal day 2. Concentrations of PL and their fatty acid (FA) profiles in the LV were analyzed in AC, sham-operated (SO) and intact animals on postnatal days 2 (intact only), 5 and 10. AC resulted in LV enlargement by 22 % and 67 % at days 5 and 10, respectively, compared with age-matched SO littermates. Concentrations of phosphatidylcholine, cardiolipin, phosphatidylinositol, phosphatidylethanolamine, phosphatidylserine and sphingomyelin decreased in AC myocardium, albeit with different time course and extent. The main effect of AC on FA remodeling consisted in the accumulation of n-3 PUFA in PL. The most striking effect of AC on FA composition was observed in phosphatidylinositol and cardiolipin. We conclude that excess workload imposed by AC inhibited the normal postnatal increase of PL concentration while further potentiating the accumulation of n-3 PUFA as an adaptive response of the developing myocardium to accelerated growth.
Keywords: novorozená zvířata; aorta abdominalis; Cell Proliferation; Constriction, Pathologic; Fatty Acids, Omega-3; myokard; Hemodynamics; Aorta, Abdominal; zvířata; Phospholipids; Rats; Animals, Newborn; Blood Pressure; mužské pohlaví; omega-3 mastné kyseliny; proliferace buněk; stenóza; krevní tlak; Rats, Wistar; krysa rodu Rattus; potkani Wistar; Animals; fosfolipidy; hemodynamika; Myocardium; Male